Allochthonous resources are less important for faunal communities on highly productive, small tropical islands. Issue 19 (26th August 2021) - Steibl, Sebastian; Sigl, Robert; Blaha, Sanja; Drescher, Sophia; Gebauer, Gerhard; Gürkal, Elif; Hüftlein, Frederic; Satzger, Anna; Schwarzer, Michael; Seidenath, Dimitri; Welfenbach, Jana; Zinser, Raphael S.; et al.
Abstract: Ecosystems are interconnected by energy fluxes that provide resources for the inhabiting organisms along the transition zone. Especially where in situ resources are scarce, ecosystems can become highly dependent on external resources. The dependency on external input becomes less pronounced in systems with elevated in situ production, where only consumer species close to the site of external input remain subsidized, whereas species distant to the input site rely on the in situ production of the ecosystem. It is largely unclear though if this pattern is consistent over different consumer species and trophic levels in one ecosystem, and whether consumer species that occur both proximate to and at a distance from the input site differ in their dependency on external resource inputs between sites. Using stable isotope analysis, we investigated the dependency on external marine input for common ground‐associated consumer taxa on small tropical islands with high in situ production. We show that marine input is only relevant for strict beach‐dwelling taxa, while the terrestrial vegetation is the main carbon source for inland‐dwelling taxa. Consumer species that occurred both close (beach) and distant (inland) to the site of marine input showed similar proportions of marine input in their diets. This supports earlier findings that the relevance of external resources becomes limited to species close to the input site in systems with sufficient in situ production. However, it also indicates that the relevance of external input is also species‐dependent, as consumers occurring close and distant to the input site depended equally strong or weak on marine input. Abstract : This work investigated the relevance of marine versus terrestrial resources for the faunal community of small tropical islands. While the beach fauna shows high proportions of marine resources to their diets, the inland fauna is largely independent of these subsidies and primarily utilizes terrestrial primary production. However, species that occurred throughout the insular ecosystems had either consistently high or low contributions of marine material to their diet, suggesting that the relevance of marine subsidies is also consumer‐dependent.